Pengaruh Model Pembelajaran Kooperatif Tipe Teams Games Tournaments terhadap Kemampuan Problem Solving Peserta Didik pada Pokok Bahasan Pancasila Kelas V SDN Dabasah 3 Bondowoso - Apriafel Gilang Budi Paranto (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research was motivated by the learning activities and problemsolvingabilities of students in classes VA and VB at SDN Dabasah 3 Bondowoso. Thelack of students' abilities, especially the ability to overcome problems (problemsolving) as well as the lack of learning strategies and media that support thelearning process where the fifth grade teacher at SDN Dabasah 3 Bondowosoonly uses lecture, discussion and question and answer learning methods duringthe learning process. The aim of this research is to find out whether or not thereisan influence of the Teams Games Tournament type cooperative learning model onstudents' problem solving abilities on the subject of Pancasila class Vat SDNDabasah 3 Bondowoso. The type of research used is Non- Equivalent Posttest Only Control Group. Data collection methods and instruments are interviewguides, documentation, test questions. and data collection instrument validationsheets, namely interview guidelines, documentation, test questions, and validationsheets. The data analysis technique used is the independent sample t-test andERtest. The average post-test score obtained in the control class was 78.89 andtheexperimental class was 89.29. The result is a p-value of less than 0.05. The ERtest got a score of 12%, so it was concluded that there was an influenceof learning using the Teams Games Tournament type cooperative learning model onstudents' problem solving abilities on the subject of Pancasila class Vat SDNDabasah 3 Bondowoso.
Entry oleh Arif 2026 Maret 25
Keywords: Problem Solving & Teams Games Tournament